2020
DOI: 10.5812/semj.97938
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Views on Service Quality in Selected Iranian Hospitals: An Importance-Performance Analysis

Abstract: Background: One of the basic steps to quality improvement in hospitals is to obtain patients’ feedback. Objectives: The aim of this study was to assess the quality of hospital services from patient’s perspective in hospitals affiliated with the Dezful University of Medical Sciences (DUMS), Dezful, Iran. Methods: In this cross-sectional study, 400 patients were selected from six hospitals of DUMS. The data was collected using the SERVQUAL questionnaire including 22 pairs of questions (organized in two aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
2
7
1
Order By: Relevance
“…This indicates that the quality of clinical forensic services at Bhayangkara Hospital, Pekanbaru did not meet patients’ expectations. This result aligns with the study conducted by Zarei et al ( 20 ), who showed a negative gap value (−0.65) for overall service quality. Good service quality should have a positive gap value, which means that patient expectations were met ( 9 , 15 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates that the quality of clinical forensic services at Bhayangkara Hospital, Pekanbaru did not meet patients’ expectations. This result aligns with the study conducted by Zarei et al ( 20 ), who showed a negative gap value (−0.65) for overall service quality. Good service quality should have a positive gap value, which means that patient expectations were met ( 9 , 15 ).…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted in Iran in 2020 obtained negative gap scores for all quality dimensions. Meanwhile, a study conducted in Taiwan in 2020 yielded more dimensions with positive gap values, specifically tangibility (0.32), empathy (0.15), and responsiveness (0.01) ( 11 , 20 ). This difference is likely because of the different indicators the studies used to assess each dimension, the different study populations and the different types of patient services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the performance of the hospitals studied did not meet patients' expectations in any aspect of hoteling services. The findings of previous studies in Iran suggested a significant gap between the perception and expectation of patients regarding the quality of hospital hoteling services (27,31), which was consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Service quality measurement can help identify weaknesses and gaps [ 17 ]. Most models and tools for measuring health service quality have been adopted from other industries [ 18 ]. One of the first and most important models is the Gronroos model (1984), which considered technical and functional quality dimensions of service quality.…”
Section: Introductionmentioning
confidence: 99%